Laser powder bed fusion of titanium-tantalum alloys : compositions and designs for biomedical applications - Huang, Sheng (2021)
In this study, laser powder bed fusion (L-PBF), also known as selective laser melting (SLM), was used to fabricate samples of titanium-tantalum (TiTa) alloys with 0, 10, 30 and 50 wt% of tantalum using in-situ alloying. As-fabricated samples comprised of randomly-dispersed pure tantalum particles in a titanium-tantalum matrix. Porosity and unmelted tantalum particles of the samples were revealed using an optical microscope (OM). The microstructure of the alloys were determined by combination of field emission scanning electron microscopy (FE-SEM), electron back scatter diffraction (EBSD) and X-ray diffraction (XRD). The mechanical properties of the alloys were investigated with tensile and Vickers hardness tests. To ascertain the suitability of these alloys as biomaterials, Ti50Ta scaffolds with 60% porosity were characterized biologically. This study further shows that porous TiTa scaffolds fabricated using L-PBF are biocompatible with comparable biological results and manufacturability as Ti6Al4V and commercially pure titanium, based on the results obtained from cell culture with human osteosarcoma cell line SAOS-2.